Gene Flow in the Müllerian Mimicry Ring of a Poisonous Papuan Songbird Clade (Pitohui; Aves) - Garg, Kritika M; Sam, Katerina; Chattopadhyay, Balaji; Sadanandan, Keren R; Koane, Bonny; Ericson, Per G P; Rheindt, Frank E (Genome biology and evolution, 2019)
Müllerian mimicry rings are remarkable symbiotic species assemblages in which multiple members share a similar phenotype. However, their evolutionary origin remains poorly understood. Although gene flow among species has been shown to generate mimetic patterns in some Heliconius butterflies, mimicry is believed to be due to true convergence without gene flow in many other cases. We investigated the evolutionary history of multiple members of a passerine mimicry ring in the poisonous Papuan pitohuis. Previous phylogenetic evidence indicates that the aposematic coloration shared by many, but not all, members of this genus is ancestral and has only been retained by members of the mimicry ring. Using a newly assembled genome and thousands of genomic DNA markers, we demonstrate gene flow from the hooded pitohui (Pitohui dichrous) into the southern variable pitohui (Pitohui uropygialis), consistent with shared patterns of aposematic coloration. The vicinity of putatively introgressed loci is significantly enriched for genes that are important in melanin pigment expression and toxin resistance, suggesting that gene flow may have been instrumental in the sharing of plumage patterns and toxicity. These results indicate that interspecies gene flow may be a more general mechanism in generating mimicry rings than hitherto appreciated.
Keywords: Pigmentation; tok genů; druhová specificita; proteiny; Phylogeny; Proteins; Biological Evolution; Gene Flow; genom; Phenotype; Songbirds; Animals, Poisonous; Genome; zvířata; pigmentace; jedovatá zvířata; fylogeneze; fenotyp; biologická evoluce; Species Specificity; zpěvní ptáci; Animals